Partial Substitution of Alfalfa Hay by Stevia (Stevia rebaudiana) Hay Can Improve Lactation Performance, Rumen Fermentation, and Nitrogen Utilization of Dairy Cows - Jiang, Maocheng; Datsomor, Osmond; Cheng, Zhiqiang; Meng, Zitong; Zhan, Kang; Yang, Tianyu; Huang, Yinghao; Yan, Qi; Zhao, Guoqi (Frontiers in Veterinary Science, 2022)
The objective of this study was to determine the effect of replacing isonitrogenous and isoenergetic basis alfalfa hay (AH) with stevia (Stevia rebaudiana) hay in dairy cow diets on nutrient digestion, milk performance, rumen fermentation, and nitrogen (N) utilization. In this study, 24 healthy Holstein lactating dairy cattle with a similar milk yield of 33.70 ± 2.75 (mean ± SD) kg, days in milk 95.98 ± 23.59 (mean ± SD) days, and body weight 587.75 ± 66.97 (mean ± SD) kg were selected and randomly allocated into three groups. The constituents of the three treatments were (1) 30.0% AH, and 0% stevia hay (SH) for the AH group; (2) 24.0% AH, and 6% SH for the 6% SH group; (3) 18.0% AH, and 12% SH for the 12% SH group. The substitution of AH with SH did not affect dry matter intake (DMI), gross energy (GE), and other nutrients intake but increased the digestibility of neutral detergent fiber (NDF) and acid detergent fiber (ADF). Compared with the AH diet, the cows fed the 6% SH diet had a higher milk yield and concentration of milk fat. Fecal and urinary nitrogen (N) were lower in cows fed a 6% SH diet than in cows fed the AH diet. Milk N secretion and milk N as a percentage of N intake were higher in cows fed a 6% SH diet than in cows fed AH diets. The concentration of ruminal volatile fatty acids, acetic acid, and ammonia-N were higher in cows fed a 6% SH diet than in cows fed an AH diet. By comparison, the 12% SH group did not affect milk yield, milk composition, N utilization, and rumen fermentation compared with the AH and 6% SH groups. In conclusion, it appears that feeding 6% SH, replacing a portion of AH, may improve lactation performance and N utilization for lactating dairy cows.